Gregory, the terrible eater - Sharmat, Mitchell; Aruego, Jose.; Dewey, Ariane (New York : Four Winds Press, 1980)
A very picky eater, Gregory the goat refuses the usual goat diet staples of shoes and tin cans in favor of fruits, vegetables, eggs, and orange juice.
Center for the Collaborative Classroom Curriculum.
K-3
490L
L
2.8
Keywords: Diet -- Fiction; Goats -- Fiction; Goats -- Fiction; Diet -- Fiction; Farm animals -- Fiction